(untitled) (Journal of Hama University, 2020)
he aim of the research is to determine the effect of the career path, one of the internal marketing strategies in its dimensions (training opportunities, responsibility, promotion, job enrichment) on the intention of working in the general company of the port in Lattakia governorate. The researcher relied on the deductive approach, and relied on the descriptive approach to characterize the research variables and analyze them based on the preliminary data that were collected, where the researcher conducted a field study on the general company of the port in Lattakia governorate to collect the necessary preliminary data, as the variables were measured on all the initial data collected Through a questionnaire that was designed by informing the researcher of previous studies and literature, and in order to test the hypotheses, In order to test the hypotheses, the researcher dumped the primary data in a database that was analyzed using SPSS version 20. One of the most important results of the study was the results of testing the four sub-hypotheses. There is a significant relationship between the dimensions of the career path (training opportunities, responsibility, promotion, and job enrichment) and the intention of work turnover, where the Pearson correlation coefficient, respectively (0.372, 0.738, 0.190, 0.212) was reached. It indicates a weak and direct correlation between the dimensions of the career path and the intention of work turnover.